KARAKTERISTIK GENTENG KOMPOSIT POLIMER BAMBU IJUK SEBAGAI MATERIAL RAMAH LINGKUNGAN DITINJAU DARI POROSITASNYA - Imam Fahmi Dian Sukma; Dzackirendy Springfield; Fajar Indra Kusuma (Politeknik Negeri Banyuwangi, 2025)
The rapid development and the advancement of technology require humans to strive for various kinds of innovations. One of them is the advancement in terms of building construction. A roof is an important part of a building. One of the innovations of roof covering is the use of a polymer composite roof. Polymer composite roof in this research was made by bamboo, palm fiber (ijuk), and resin 157 BQTN and catalyst. This research was objected to explore the influence of palm fiber length and the concentration of catalyst use towards porosity in a roof with composite materials and the minimum porosity produced by the optimum palm fiber length a roof with composite materials. The research employed a quantitative method by experiment approach. The variations in the research were 5 cm, 15 cm, and 30 cm of palm fiber length and the variations of catalyst concentration toward the volume of resin were 3%, 5%, and 7%. The test specimens of porosity which have 200x300x3 mm in dimension with a total of 36 samples. The results of this research showed that there was no effect on palm fiber variations and the concentration of catalyst use toward the porosity of polymer composite roof and the minimum porosity was 0.21%; optimally produced at 30 cm palm fiber length variation and 5% catalyst concentration.